Due Diligence in Financial Aspects for Mobile Fuel Station Business Development - Saputra, Edwin Tri Angga; Indradewa, Rhian; Negoro, Dimas Angga; Hamdi, Edi (Dynamic Management Journal, 2024)
The fuel sales of motorcycle experience complex dynamics, particularly in satisfying consumer demand for leanness and ease of service. The Mobile Fuel Station (MFS) service innovation, powered by information technology, was created to accelerate the establishment of new sales outlets and enhance the efficiency and convenience of consumer service. However, this option requires substantial expenses, necessitating due diligence on the financial side. The objective of this study is to evaluate and ensure the feasibility of the Mobile Fuel Station Investment Program (PI MFS). The research findings indicate that the Return on Investment (ROI) is 18.46%, with a positive Net Present Value (NPV) and an Internal Rate of Return (IRR) of 23.42% in the sixth year so that PI MFS is feasible to implement. To shorten short-term debt obligations, PI MFS has a current ratio of 2.64 times. Additionally, a 32.06% DER value indicates that a greater proportion of its financing comes from equity rather than debt. This research provides direction for the future development of more efficient managerial practices, as well as generates investor interest by demonstrating the potential for growth and profitability.